1998
DOI: 10.1007/s11745-998-0292-9
|View full text |Cite
|
Sign up to set email alerts
|

Divergent incorporation of dietary trans fatty acids in different serum lipid fractions

Abstract: Trans fatty acids may be involved in atherosclerotic vascular diseases. We investigated the incorporation of dietary trans fatty acids and oleic acid into the serum triglycerides (TG), cholesterol esters (CE), and phospholipids (PL). Fourteen healthy female volunteers, aged 23.2+/-3.1 yr (mean+/-SD), body mass index 20.8+/-2.1 kg/m2 participated in this study. All subjects consumed both a trans fatty acid-enriched diet (TRANS diet) and an oleic acid-enriched diet (OLEIC diet) for 4 wk according to a randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
7
23
0
Order By: Relevance
“…From this difference arise their different physiological effects: trans isomers are similar to saturated fatty acids, while cis isomers have more beneficial effects. As cis and trans fatty acids use the same enzymes during their metabolism, several studies have indicated, that trans fatty acids may disturb the metabolism of the physiologically important n-3 and n-6 fatty acids (Szabó et al, , 2010aVidgren et al, 1998). Fig.…”
Section: Biochemistry Of Fatty Acidsmentioning
confidence: 99%
“…From this difference arise their different physiological effects: trans isomers are similar to saturated fatty acids, while cis isomers have more beneficial effects. As cis and trans fatty acids use the same enzymes during their metabolism, several studies have indicated, that trans fatty acids may disturb the metabolism of the physiologically important n-3 and n-6 fatty acids (Szabó et al, , 2010aVidgren et al, 1998). Fig.…”
Section: Biochemistry Of Fatty Acidsmentioning
confidence: 99%
“…Biological markers of fat intake offer an alternative to assessing TFA exposure because tissue fatty acid composition reflects actual rather than reported intake, thus avoiding the particular problems of quantifying 'hidden' fats or the well-established underreporting of fat intake (Beaton et al, 1979;Bingham, 1987;Bingham et al, 1994). Biomarkers of TFA intake are particularly good (Vidgren et al, 1998;Lichtenstein et al, 2003) because there is negligible endogenous synthesis of TFAs and there is a dose-response relation with dietary intake (Mensink and Hornstra, 1995). There are examples of biomarkers being used to monitor changes in population intakes of TFAs over time (Innis et al, 1999;Clifton et al, 2004;Colon-Ramos et al, 2006).…”
Section: Monitoring Compliancementioning
confidence: 99%
“…Beyond cardiovascular disease risk, another concern about trans fatty acids is theoretical at present. In both animal and human studies, dietary trans fatty acids have been determined to be digested, absorbed and incorporated into serum triglycerides, cholesterol esters, phospholipids, lipoproteins and adipose tissue, 10, [30][31][32] or platelets, 33) in the same way as natural cis isomers.…”
Section: Other Risks Of Trans Fatty Acidsmentioning
confidence: 99%